The effect of quantitative easing on US sector returns - Lehmann, Kristóf; Neszveda, Gábor; Molnár, Tamás (Public Finance Quarterly, 2023)
In this study, we used event analysis to examine whether abnormal returns can be observed for US sector returns at the time when quantitative easing was announced. In our investigation, we sought to identify the sectors in which the amount of money introduced into the economy as a result of quantitative easing. In addition, since the programme is basically implemented by the central bank in order to stabilise the economy, an examination of its effect on the sectors may provide guidance on which segments have reacted negatively, thus possibly requiring additional central bank or public intervention. In our results, we found consistency for all four QE programme in some sectors In the examination of the S&P 500 sector indices, surprisingly no significant abnormal return was found in the financial sector, by contrast, for the healthcare sector, as well as discretionary and general consumer goods, the stocks included in the sector index reacted in the same way for all 4 announcements.